2019
DOI: 10.24293/ijcpml.v25i2.1377
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Spesific Enolase Serum Levels and Outcome Acute Ischemic Stroke Onset 1-Month

Abstract: Pendahuluan: Stroke adalah masalah kesehatan global, karena penyebab kematian kedua dan kecacatan utama pada hampir seluruh negara di dunia. Penyakit ini memiliki dampak yang besar terhadap penderita, lingkungan sosial dan beban ekonomi. Sehingga diperlukan penanda spesifik yang berperan dalam menegakkan diagnosis, penentuan faktor risiko, serta tingkat keparahan stroke iskemik. Salah satu penanda yang diteliti adalah kadar NSE serum, yang diperkirakan dapat menggambarkan beratnya kerusakan otak pada pasien st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In terms of functional outcomes, included studies used different methods to assess functional outcomes such as Barthel index, Lindley scale, modified Rankin Scale (mRS), Glasgow Outcome Score, and activities of daily living scale. Three studies 22,32,35 reported a notable correlation between NSE and functional outcome. Moreover, Pandey et al, 14 and Bharosay et al 25 concluded that the higher the NSE level, the more significant functional worsening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of functional outcomes, included studies used different methods to assess functional outcomes such as Barthel index, Lindley scale, modified Rankin Scale (mRS), Glasgow Outcome Score, and activities of daily living scale. Three studies 22,32,35 reported a notable correlation between NSE and functional outcome. Moreover, Pandey et al, 14 and Bharosay et al 25 concluded that the higher the NSE level, the more significant functional worsening.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the findings of nine out of the 12 included studies in the current meta-analysis, which showed that NSE levels were meaningfully higher in stroke patients than in the control group while, other three included studies showed no significant difference between NSE and control. 28,34,35 This contrast might be explained by the slow released of NSE from damaged tissue to peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…NSE with its longer half-life in blood compared to other biomarkers, can indicate the presence of brain inflammatory processes and neuronal cell death. High levels of NSE are associated with neuronal cell injury [ 16 ].…”
Section: Introductionmentioning
confidence: 99%